Damage Types and Deterioration Characteristics of Check Dams Built on Mountain Streams in Southeast Korea - Lee, Ki-Hwan; Ewane, Ewane Basil; Uchida, Taro; Woo, Choong-Shik (Frontiers in Earth Science, 2022)
Check dams are one of representative structural measures to reduce sediment disaster at a forest watershed. Therefore, it is essential to assess the structural vulnerability and functionality of check dams in the management of sediment disaster risk at watersheds. This study examined the main types of damages and deterioration characteristics in concrete and stone check dams, which comprise more than 80.0% of Korea’s check dam stock. This was based on the 4-step condition assessment, which is the modified version of condition assessment methodology for embankment dams to meet the characteristics of check dams. As a result, the damages and deterioration of concrete check dams were classified into ten representative types. And representative damage types of stone check dams were classified into nine types. The condition assessment results demonstrated that the spillway part frequently contacted with water and debris flows was deteriorated approximately 1.2 times faster than the wing parts for both concrete and stone check dams, and the maintenance demands of both types of check dams increased 15-20 years after construction. Thus, these deterioration characteristics of concrete and stone check dams should be considered in decision-making to determine maintenance priorities among the check dams stock. Furturemore, we analyzed the relationship between condition index and service time in the examined concrete and stone check dams. The degree of deterioration in concrete and stone check dams increased significantly as the service time increased. Based on the relationship between condition index and service time, we classified deterioration characteristics of check dams into two groups: (1) those that follow the average deterioration trends of their facility group (Group II) and (2) those that undergo an unexpected end-of-service life because of exceptional incidents or severe defects (Group I). We hope that our work will form a useful resource for engineers and decision-makers involved in planning, designing, constructing, and maintaining check dams.